Respostas
respondido por:
466
x-y = 5
x+y=7
x - y = 5 ---> x = y + 5
Substituindo na segunda equação acima:
y + 5 + y = 7
2y = 7 - 5
2y = 2
y = 1
Agora substituindo na equação: x = y + 5
x = 1 + 5
x = 6
x+y=7
x - y = 5 ---> x = y + 5
Substituindo na segunda equação acima:
y + 5 + y = 7
2y = 7 - 5
2y = 2
y = 1
Agora substituindo na equação: x = y + 5
x = 1 + 5
x = 6
joaofernando:
valeu
respondido por:
258
{x - y = 5
{x + y = 7
x - y = 5
x = 5 + y
x + y = 7
(5 + y) + y = 7
5 + y + y = 7
y + y = 7 - 5
2y = 2
y = 2/2
y = 1
x = 5 + y
x = 5 + 1
x = 6
S = {6, 1}
{x + y = 7
x - y = 5
x = 5 + y
x + y = 7
(5 + y) + y = 7
5 + y + y = 7
y + y = 7 - 5
2y = 2
y = 2/2
y = 1
x = 5 + y
x = 5 + 1
x = 6
S = {6, 1}
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás